Assessment of Musculoskeletal Disorders Prevalence Among Dentists - Kh.Dehghan Tezerjani; MH.AkhavanKarbasi; A.Haerian Ardakani; F.Ezoddini Ardakani (Tehran University of Medical Sciences, 2005)
Statement of Problem: According to many researches done in the field of occupational disorders dentists are considered at the risk of musculoskeletal problems. These problems may cause reduction of job length of dentists.Purpose: This study was done for evaluating the musculoskeletal disorders of dentists, practicing in Yazd.Materials and Methods: This is a descriptive cross-sectional study, conveyed in Yazd city in 1999 by survey among all of working dentists with eye-to-eye contact questionnaire reply.Results: Among dentists were interviewed 81.6% of respondents mentioned at least one of musculoskeletal problems. The mentioned disorders were respectively; Neck (47.1%) hand (36.2%), wrist (34.8%), upper and lower parts of back (33.3%), shoulder (11.59%), knee (2.8%). About 72.5% of the individuals had no familial history and just 4.5% had these disorders before working as a dentist.Conclusion: Results of this study revealed that majority of musculoskeletal disorders had significantrelationship with age, gender, work place, working hours, level of exercise, direct vision and duration of the job of dental occupation.